PRECAMBRIAN-CAMBRIAN BOUNDARY CANDIDATE, ALDAN RIVER, YAKUTIA, U.S.S.R - Rozanov A.Y.; Cowie J.W. (My University, 1983)
The current situation in 1982 regarding the status and validity of the Ulakhan-Sulugur section on the Aldan River as a candidate for the global stratotype section and point for the Precambrian-Cambrian (PC-C) Boundary is reviewed with details of new work since 1973 and consequent revisions of views on controversial topics on a regional, continental and intercontinental scale of stratigraphic correlations with a short note regarding accessibility.
Keywords: Precambrian; Cambrian; Precambrian; Paleozoic::Cambrian; Палеозой::Кембрийская; Докембрий